2022
DOI: 10.1097/md.0000000000028618
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of parenteral nutrition (PN) and enteral nutrition (EN) supports in cirrhosis

Abstract: Importance: Multiple nutritional therapies are currently available for patients with liver cirrhosis, yet many interventions have not been compared head-to-head within randomized clinical trials. Objective: To evaluate the improvement of nutritional indicators and liver function indexes of liver cirrhosis treated with different nutrition intervention. Data source: We searched PubMed, Embase. com and Cochrane Library database from construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, supplementation with probiotics may, on the one hand, promote the growth of beneficial bacteria and, on the other hand, limit the growth of undesirable bacteria and the production of their harmful metabolites while supporting intestinal transport [ 141 , 142 ]. Based on the results of a meta-analysis and a network meta-analysis, Yu et al [ 119 ] concluded that EN+ gut probiotics may be the most effective intervention, relatively speaking. In patients with cirrhosis, antibiotic therapy is often necessary, which leads to an imbalance of the intestinal flora, which results in the generation of enterotoxins and the metabolites of pathogenic microflora [ 119 ].…”
Section: Nutritional Support For Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, supplementation with probiotics may, on the one hand, promote the growth of beneficial bacteria and, on the other hand, limit the growth of undesirable bacteria and the production of their harmful metabolites while supporting intestinal transport [ 141 , 142 ]. Based on the results of a meta-analysis and a network meta-analysis, Yu et al [ 119 ] concluded that EN+ gut probiotics may be the most effective intervention, relatively speaking. In patients with cirrhosis, antibiotic therapy is often necessary, which leads to an imbalance of the intestinal flora, which results in the generation of enterotoxins and the metabolites of pathogenic microflora [ 119 ].…”
Section: Nutritional Support For Liver Diseasesmentioning
confidence: 99%
“…Based on the results of a meta-analysis and a network meta-analysis, Yu et al [ 119 ] concluded that EN+ gut probiotics may be the most effective intervention, relatively speaking. In patients with cirrhosis, antibiotic therapy is often necessary, which leads to an imbalance of the intestinal flora, which results in the generation of enterotoxins and the metabolites of pathogenic microflora [ 119 ].…”
Section: Nutritional Support For Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation